“MENYEMBAH ALLAH DALAM ROH DAN KEBENARAN” (YOHANES 4:20-26): SEBAGAI SUATU LANDASAN PRAKTEK IBADAH KRISTEN YANG ALKITABIAH: "WORSHIP GOD IN SPIRIT AND TRUTH" (JOHN 4: 20-26): AS A BASIS OF THE PRACTICE OF CHRISTIAN WORSHIP - Toni Irawan (Jurnal Teologi Amreta (ISSN: 2599-3100))
Worship is not merely a routine ceremonial activity in the lives of Christians. Worship is in fact a meeting between the Church and God. In addition, worship is also an important means of reviving and strengthening the beliefs of the congregation, and to spread the love of Christ to those who do not know Christ. The logical consequence of this realization is the effort to build worship practices on top of the right perspective foundation. From the study of the meaning of "worshiping God in spirit and righteousness" in John 4:20-26, the theological implications were finally found for the establishment of biblical worship. Firstly, the essence of worship is no longer centred on a place or liturgy, but to Jesus himself who is none other than God. Second, worship centred on God. Third, worshiping God in spirit and truth is essentially happening not solely because of the encouragement of the human spirit or the sincere attitude of man. But more than that, true worship occurs when the Holy Spirit moves or empowers people to worship God. Thus, a new believer can be involved in true worship when Christ is full sovereign as his personal saviour. True worship also brings the believer to the earnest fulfilment of Christ's existence in his life. Thus worship or worship is not destined to satisfy man, but to glorify God. True worship will ultimately lead believers to preach Christ whom he has known to unbelievers. ==== Ibadah bukanlah sekedar aktivitas seremonial rutin dalam kehidupan orang Kristen. Ibadah pada hakikatnya merupakan perjumpaan antara jemaat dengan Allah. Selain itu, ibadah juga merupakan sarana yang penting untuk menghidupkan dan menguatkan kepercayaan jemaat, dan untuk menyinarkan kasih Kristus kepada orang-orang yang belum mengenal Kristus. Konsekuensi logis dari kesadaran ini adalah usaha membangun praktik ibadah di atas fondasi prespektif yang benar. Dari kajian terhadap makna “Menyembah Allah dalam Roh dan kebenaran” dalam Yohanes 4:20-26, pada akhirnya ditemukan implikasi teologis bagi usaha menyelenggarakan ibadah yang Alkitabiah. Pertama, esensi penyembahan bukan lagi berpusat kepada tempat ataupun liturgi, namun kepada Yesus sendiri yang tidak lain adalah Allah. Kedua, penyembahan yang dipusatkan kepada Allah. Ketiga, menyembah Allah dalam Roh dan kebenaran pada dasarnya terjadi bukan semata-mata karena dorongan roh manusia atau sikap tulus manusia. Namun lebih dari itu, penyembahan yang benar terjadi pada saat Roh Kudus menggerakkan atau memberdayakan manusia untuk menyembah Allah. Dengan demikian, umat percaya baru dapat terlibat dalam penyembahan yang benar apabila Kristus berdaulat penuh sebagai Juruselamatnya pribadi. Penyembahan yang benar juga membawa umat percaya kepada pengenalan yang sungguh-sungguh akan keberadaan Kristus dalam kehidupannya. Dengan demikian penyembahan atau ibadah bukanlah diperuntukkan untuk memuaskan manusia, namun untuk memuliakan Allah. Penyembahan yang benar pada akhirnya akan menuntun umat percaya untuk memberitakan Kristus yang telah dia kenal kepada orang-orang yang belum percaya.